Le savoir de l’Autre : un naturaliste français en Nouvelle-Grenade au xixe siècle - Daniel López (Viatica)
The French naturalist Charles Saffray visited New Granada (now Colombia) in the mid-19th century. This travel writing through the Andean country was first published in the famous magazine Le Tour du Monde between 1872 and 1873 in several instalments decorated with some maps and several pictures, under the title « Voyage à la Nouvelle-Grenade par M. Le Docteur Saffray ». The comments about the vestiges, customs and medicinal and botanical knowledge of the natives are a striking feature in his account. It is this aspect that we would like to address in this article, with the aim of detecting the way in which the French traveller approached the knowledge that these peoples held of a habitat rich in natural resources.